Analisis Strategi Penghimpunan Dana Zakat Lembaga Amil Zakat Nasional Baitul Maal Hidayatullah (Laznas BMH) - Abdul Wahid Mongkito (IAIN Palopo, 2019)
Referring to a study conducted by the National Amil Zakat Agency BAZNAS in cooperation with the Bogor Agricultural University (IPB) in 2011, it was revealed that the potential of zakat Indonesia amounted to 217 trillion dollars and will continue to grow each year. But the magnitude of the potential can’t be exploited by BAZ and LAZ were already there. Zakat manager need strategies to optimize zakat fundraising. Through the study of internal factors and external factors LAZNAS BMH organization, an analysis of Internal and External Factors Evaluation in order to obtain the right strategy to be done by the organization LAZNAS BMH although still common. Further research conducted by TOWS matrix to get some viable strategy undertaken by LAZNAS BMH, then choose the best strategy of the proper strategies conducted by LAZNAS BMH with Quantitative Strategy Planning Matrix (QSPM) analysis method, that is: to socialize so that Muslims are interested in LAZNAS BMH, expanding the scope of the zakat, as well as making zakat fund raising strategies and methods of the target receipt of zakat funds